A case of primary aldosteronism with resistant hypertension successfully treated by unilateral adrenalectomy after unsuccessful classification of subtype in adrenal venous sampling. Issue 10 (22nd August 2019) - Nakamaru, Ryo; Yamamoto, Koichi; Nozato, Satoko; Hongyo, Kazuhiro; Nagasawa, Motonori; Hagiya, Hideharu; Nakagami, Futoshi; Akasaka, Hiroshi; Kurinami, Hitomi; Takami, Yoichi; Takeya, Yasushi; Sugimoto, Ken; et al.
Abstract: Despite being an established method to identify the unilateral subtype of primary aldosteronism with an indication of adrenalectomy, adrenal venous sampling sometimes fails primarily due to unsuccessful cannulation to adrenal veins. In such cases, the analysis of clinical findings might help to identify the indication of surgery. Abstract : Despite being an established method to identify the unilateral subtype of primary aldosteronism with an indication of adrenalectomy, adrenal venous sampling sometimes fails primarily due to unsuccessful cannulation to adrenal veins. In such cases, the analysis of clinical findings might help to identify the indication of surgery.